BMI and Nutritional Status in Physical Active Population Involved in Recreational Sport - Fidanka Vasileva; Daniela Shukova-Stojmanovska; Angjel Vasilev; Georgi Georgiev (University of Montenegro, Faculty for Sport and Physical Education, Montenegrin Sports Academy, 2022)
Practice of sport, exercise or recreational physical activity increase the needs of energy and nutrients. Objectives are: 1) to evaluate BMI; 2) to assess the nutritional status; and 3) to test the association between BMI and KIDMED index. The study is realized on a sample of healthy young participants (N=101), aged 18 - 35, that do recreational sport activities such as: football (N=24), basketball (N=16), handball (N=15), volleyball (N=20), tennis (N=10), swimming (N=10) and martial arts (N=9). Body composition: height, weight, and BMI, were measured and calculated according to World Health Organization's manual. A 16-item KIDMED questionnaire was used to assess nutritional status. KIDMED index was calculated after the KIDMED questionnaire was administered to all participants. Spearman's rank correlation coefficient was applied to test the association between BMI and KIDMED index. We have assessed an optimal diet - medium quality, in physically active population that is involved in recreational sport such as: football, basketball, handball, volleyball, tennis, swimming and martial arts, and a normal healthy weight category based on BMI classification criteria of World Health Organization. In addition, we have found a weak positive association between BMI and KIDMED index in physically active population, that was not statistically significant. The outcome of the study indicates that most of the people that are regularly involved in physical activity have a decent nutritional awareness, as a result of the nutritional counseling they get from their coaches. It seems that recreational collective activities and sports, besides allowing people to gain knowledge about healthy eating skills and nutritional habits, also encourage them to bring the required changes in their diets. The impact of physical activity may be a promising area for future promotion of nutrition and health.